Research on rheumatic heart disease from 2013 to early 2024: a bibliometric analysis - Yifan Chen; Liuding Wang; Dan Ma; Zhijie Cui; Yanjiao Liu; Qinghua Pang; Zhonghui Jiang; Zhuye Gao (Journal of Cardiothoracic Surgery)
Abstract Objectives The aim of this bibliometric analysis was to highlight potential future areas for the practical application of research on rheumatic heart disease (RHD), considering past and current research efforts. Methods A systematic search was conducted in the WoSCC to find articles and reviews focused on RHD published between 2013 and 2024. Microsoft Excel 2019 was used to chart the annual productivity of research relevant to RHD, while ArcGIS (version 10.8) was employed to visualize the global distribution of publications. Analysis tools such as CiteSpace (version 6.1.R6) and VOSviewer (version 1.6.18) were utilized to identify the most prolific countries or regions, authors, journals, and resource-, intellectual-, and knowledge-sharing in RHD research, and to perform co-citation analysis of references and keywords. Additionally, the Bibliometrix R Package was used to analyze topic dynamics. Results From the search, a total of 2,428 publications were retrieved. In terms of countries or regions, the United States was the most productive country (566, 23.31%). As for institutions, most publications have been contributed by the University of Cape Town (149, 6.14%). Regarding authors, Jonathan R. Carapetis produced the most published works, and he received the most co-citations. The most prolific journal was identified as the International Journal of Cardiology (70, 2.88%). The study published in Circulation received the most co-citations. Keywords with ongoing strong citation bursts included “surgical treatment” and “valvular heart disease”. Conclusion Despite the rapid advancements in the field of RHD research, future efforts should prioritize strengthening collaboration among national institutions to facilitate information dissemination. Current research on RHD mainly focuses on prognosis of patients. While, the emerging research trends in RHD encompass treatment strategies for complications, including atrial fibrillation (AF), heart failure (HF), and infective endocarditis, as well as screening strategies for RHD and surgical interventions for patients with rheumatic mitral valve disease.